Cd in planktonic and benthic foraminiferal shells determined by thermal ionisation mass spectrometry - Rickaby, R; Greaves, M; Elderfield, H (2000)
A highly sensitive method for Cd determination in foraminiferal shells by isotope-dilution TIMS has been developed and applied to (i) a more detailed reconstruction of seawater Cd depth profiles for the North Atlantic in the Holocene and at the Last Glacial Maximum (LGM); (ii) the analysis of Cd/Ca in individual benthic foraminifera shells; and (iii) determination of Cd/Ca in Holocene and glacial planktonic foraminifera. Although Cd has a high first ionisation potential, through chemical separation of Cd from the Ca and optimisation of the loading technique, it is possible to analyse routine sized samples (10 benthics) with a reproducibility in Cd/Ca of ± 0.0025 μmol/mol between replicate picks from a single sample. The blank of the method is 1.1 pg, permitting analysis of individual benthics and of planktonic foraminifera. The seawater Cd reconstruction for the LGM is consistent with previous work, but also suggests that depths > 2500 m were ventilated by a northern source of nutrient depleted deep water on the western side of the Mid Atlantic Ridge. Individual benthic Cd/Ca ratios show interspecimen variability which is averaged in routine analysis of multiple specimens. Planktonic Cd/Ca from N. Atlantic cores shows interspecific differences between Globigerina bulloides and Neogloboquadrina pachyderma and Holocene-LGM contrasts which offers potential for use of planktonic Cd/Ca as a palaeochemical tracer. Copyright (C) 2000 Elsevier Science Ltd.